Exploring the Relationship Between Work Motivation and Generation Z Employee Performance: A Study at Cafe Quest Cikarang Billiards - Nur Saputra Tri Caesar (Lentera Ilmu Nusantara, 2025)
This study examines the effect of work motivation on the performance of Generation Z employees at Cafe Quest Cikarang Billiard. The study population was all Gen Z employees at the cafe, with a sample size of 23 people. Data were collected through an online questionnaire using Google Form . Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) through SmartPLS 3 software . The results showed that work motivation has a positive and significant effect on the performance of Generation Z employees. This finding emphasizes the importance of motivational strategies that are appropriate to the characteristics of the younger generation in improving performance in the entertainment service sector .